Exploring the catchment area of an urban railway station by using transit card data: Case study in Seoul. (December 2019) - Eom, Jin Ki; Choi, Jungsoon; Park, Man Sik; Heo, Tae-Young
Abstract: To enhance transit ridership, Seoul introduced a transfer discount fare scheme that uses an automated fare collection system in Seoul 2004. The transfer discount fare system records all transfer information between rail and buses in transit smartcard data, which enabled us to explore an urban railway station's catchment area. In this study, we examined the geographic distribution of rail-to-bus transfer trips and their characteristics by using transit smartcard data. Mokdong station in Seoul was used as a case study to demonstrate the benefits of data mining for the depiction and easy evaluation of a station's catchment area. The results showed that the average transfer passenger traveled 1.7 km with five bus stops after boarding to access the business district during the morning peak hour. The cumulative distribution of alighting passengers by bus route helped with inferring the shape and size of the urban railway station's catchment area in each direction and depending on the time of day. We found that reliable transfer travel data constitute valuable information for evaluating an urban railway station's catchment area with respect to the type of land use and will help transit agencies with providing better transit services in terms of enhanced accessibility by changing bus headways and routes, as well as land use planners with evaluating transit-oriented development based on the expanded concept of a metro station's catchment area. Highlights: Demonstrating the way of visualization of station's catchment area using transport card data Examining the shape and size of the urban railway station's catchment area by time-of-day scheme Comparing transfer distance between routes and their directions Comparing rail-to-bus transfer patterns by the service group of bus routes Potential use of transport card data for planning transit-oriented development